Emotional Intelligence in Relation to Academic Achievement - Sharma, Anjali (JOURNAL OF INDIAN EDUCATION, 2014)
The present study is an attempt to study whether the students of different academic achievement level have the same emotional intelligence and examine if there is any correlation between the two variables — EQ and academic achievement. Null hypothesis were formulated against the objectives, and the normative survey method was used to conduct the study. Data was collected using stratified random sampling method. A total sample of 240 students (both male and female,) studying in class 11th from all disciplines, science, arts and commerce, was taken and the schools from both urban and rural areas have been chosen. Emotional intelligence inventory was used to measure the EQ of the students, and marks obtained in the annual examination of Class X was used to form groups according to their academic achievements. The result showed that emotional intelligence is an independent variable from not only academic achievement but gender as well. Thus, the finding reveals the insignificant correlation between emotional intelligence and academic achievement.